Effect of the mandatory vaccination law on measles and rubella incidence and vaccination coverage in Italy (2013-2019) - Alessandro Sindoni; Valentina Baccolini; Giovanna Adamo; Azzurra Massimi; Giuseppe Migliara; Corrado De Vito; Carolina Marzuillo; Paolo Villari (Taylor & Francis Group, 2022)
Despite the introduction of the trivalent vaccine (measles, mumps, rubella) more than 20 years ago, measles outbreaks have occurred in Europe, including Italy, due to its underutilization. In Italy mandatory vaccination was established in 2017 (Decree Law 119/2017). This study aimed at evaluating the impact of mandatory vaccination and determining the trend in vaccination coverage for measles and rubella in Italy. We retrieved data from the Annual Status Update, a form sent annually by the Italian National Verification Committee to the Regional Verification Committee for Europe, from 1st January 2013 to 31st December 2019. Since the beginning of 2013, 14,788 cases of measles have been reported, ranging from 256 (3.9 x 1,000,000) to 5,397 (88.4 x 1,000,000) compared to 259 rubella cases for the same period. From 2013 to 2015, vaccination coverage decreased for the first dose of measles (90.4% to 85.3%) and rubella vaccine (90.3% to 85.2%), but then it increased significantly, reinforced by the Italian Decree Law, reaching 94.4% in 2019. The trend for the second dose showed a decrease from 2013 to 2016 (84.1% to 82.2% for measles and 83.7% to 82.0% for rubella), but then increased significantly and reached 90.2% in 2019 for measles and 90.0% for rubella. The mandatory vaccination law has resulted in a significant increase in vaccination coverage for measles and rubella in Italy, and demonstrates encouraging progress toward the 95% target and the restriction of measles transmission. Special attention should be paid to maintaining and further improving vaccination coverage.